Carteira digital para todos: análise de usabilidade e prototipação de aplicativo móvel como meio de pagamento inclusivo e acessível - Nakanishi, Bruna (2022)
This dissertation aims to explore the relationship people have with their smartphones and payment methods in mobile applications; it also aims to analyze application projects developed by the market and bibliographic investigations to elucidate issues of perception, accessibility, usability and digital design. Based on the research, a prototype of a digital wallet mobile application is built, focused on elderly and/or low vision (visually impaired) people, respecting the accessibility rules of contrast and text resizing to seek to discuss how current technologies affect the lives of this group, and how design fits in as a tool to facilitate access to payment methods today